(untitled) (Journal of Comparative & International Higher Education, 2022)
Emotional Intelligence (EQ) is a multifaceted ability that helps us to sense, understand, value, and effectively apply the power of emotions as a source of information, trust, creativity, and influence (Goleman, 2006; Salovey, Caruso, & Cherkasskiy, 2011). The five components (self-awareness, self-regulation, empathy, motivation, and social skill) embedded within EQ may work solely or collectively and may individuals cope with everyday life events. Such an emotional tool kit may help multicultural international students to help cope with several adverse situations. The focus of this study was to provide an auto-ethnographic account of a female university student’s experiences as she transitions to become a full-time international graduate student in an Ontario university. The author reflects on the hurdles and socio-emotional challenges experienced during the transition to becoming a graduate student in Ontario. Overall, based on the student’s experiences, findings suggest the need for Canadian universities to incorporate multiple components of EQ into their international university services, including mindfulness, self-regulation, and stress management.